"You are stealing our present": Younger people's ageism towards older people predicts attitude towards age‐based COVID‐19 restriction measures. (9th August 2022) - Spaccatini, Federica; Giovannelli, Ilaria; Pacilli, Maria Giuseppina
Abstract: The COVID‐19 pandemic emerged to be a fertile ground for age‐based prejudice and discrimination. In particular, a growing literature investigated ageism towards older people at the individual and the interpersonal level, providing evidence of its prevalence, antecedents and negative consequences. However, less much is known on the phenomenon at the intergroup level. To fill this gap, the present correlational research investigated the effects of younger people's endorsement of ageism towards older people on the attitude towards COVID‐19 restriction measures primarily targeted to older (vs. younger) population. In the autumn of 2020, five hundred and eighty‐two Italian participants (83.3% females; M age = 20.02, SD age = 2.83) completed an online questionnaire. Results revealed that the younger people's endorsement of ageism towards older people increased the attribution of culpability for the severity of COVID‐19 restriction measures to older (vs. younger) people, which, in turn positively affected the attitudes towards older (vs. younger) people isolation and support for selective lockdown on older population only. The main contributions of the study, limitations, future research directions, and practice implications are discussed.